An Integrated Computational and Experimental Approach to Formulate Tamanu Oil Bigels as Anti-Scarring Agent - Megha Krishnappa; Sindhu Abraham; Sharon Caroline Furtado; Shwetha Krishnamurthy; Aynul Rifaya; Yahya I. Asiri; Kumarappan Chidambaram; Parasuraman Pavadai (MDPI AG, 2024)
Tamanu oil has traditionally been used to treat various skin problems. The oil has wound-healing and skin-regenerating capabilities and encourages the growth of new skin cells, all of which are helpful for fading scars and hyperpigmentation, as well as promoting an all-around glow. The strong nutty odor and high viscosity are the major disadvantages associated with its application. The aim of this study was to create bigels using tamanu oil for its anti-scarring properties and predict the possible mechanism of action through the help of molecular docking studies. In silico studies were performed to analyze the binding affinity of the protein with the drug, and the anti-scarring activity was established using a full-thickness excision wound model. In silico studies revealed that the components inophyllum C, 4-norlanosta-17(20),24-diene-11,16-diol-21-oic acid, 3-oxo-16,21-lactone, calanolide A, and calophyllolide had docking scores of −11.3 kcal/mol, −11.1 kcal/mol, −9.8 kcal/mol, and −8.6 kcal/mol, respectively, with the cytokine TGF-β1 receptor. Bigels were prepared with tamanu oil ranging from 5 to 20% along with micronized xanthan gum and evaluated for their pH, viscosity, and spreadability. An acute dermal irritation study in rabbits showed no irritation, erythema, eschar, or edema. In vivo excisional wound-healing studies performed on Wistar rats and subsequent histopathological studies showed that bigels had better healing properties when compared to the commercial formulation (MurivennaTM oil). This study substantiates the wound-healing and scar reduction potential of tamanu oil bigels.